Fatal and non-fatal inflammatory injuries induced by different concentrations of L-arginine in Kunming rats - Chunxia Li; Ge Zhang; Aijun Dai; Xiuyan Wang (SAGE Publishing, 2018)
To establish animal models of fatal and non-fatal pancreatitis, we randomly divided 55 Kunming rats into three groups: Group A received three intraperitoneal injections of 8% L-arginine (L-arg); Group B received three intraperitoneal injections of 10% L-arg; and Group C (the control group) received three intraperitoneal injections of saline. After the third injection, biochemical indices and pathological changes in the pancreas and lungs were evaluated. In Group A, the rats experienced peak inflammatory edema at 48 h after the injections and exhibited the highest pathological score, but the biochemical indices showed no phase-related changes. In Group B, the rats exhibited significantly increased biochemical indices at 12 h after injection and experienced peak inflammatory edema at 24 h; the pathological score was also the highest, significantly different from the observations for Groups A and C ( P  < 0.05), and the mortality rate was 64% over 72 h. Thus, it was inferred that L-arg could be used to establish pancreatitis models and that different concentrations lead to different lesions.